Factors Contributing to Prolonged Hospitalization of Patients With Infantile Hypertrophic Pyloric Stenosis - Kuo-Shu Tang; I-Fei Huang; Hsiang-Hung Shih; Ying-Hsien Huang; Chi-Hung Wu; Chung-Ching Lu; Fu-Chen Huang; Mao-Meng Tiao; Chi-Di Liang (Elsevier, 2011)
To study the influence of clinical audit on diagnosis, complications, and factors contributing to hospitalization of patients with infantile hypertrophic pyloric stenosis. Study Design: Retrospective cohort study. Method: There were 214 patients from 1991 to 2004 from three medical centers in Kaohsiung. Data were analyzed with respect to diagnostic methods, complications, and factors requiring patient hospitalization. Results: The ratio of male to female was 4.8:1 (177 males and 37 females). The diagnoses before admission were as follows: 22% had milk intolerance and 14.5% had esophageal reflux. There was a significant increase in the use of sonogram diagnostic test (p=0.005) and a decrease in the incidence of diagnosis by olive mass palpation but not by barium meal test. Surgery time of 48 hours after admission was significant with barium meal examination and related to longer hospital stay (p<0.001). Weight gain less than 800 g before admission (n=125) was related to longer hospital stay (p=0.026). Conclusion: The diagnostic method was changed from olive mass palpation to sonogram. Weight gain less than 800 g before admission and surgery time of 48 hours after admission were related to longer hospital stay.